COMPARATIVE FINANCIAL PERFORMANCE OF BANK SYARIAH INDONESIA AND BANK ACEH SYARIAH: AN EVA APPROACH - Arifin, Muhammad; Siregar, Putri Bungsu; Insani, Muhammad Fitrah (Journal of Sharia Economics, 2026)
This study examines and compares the financial performance of Bank Syariah Indonesia (BSI) as a national Islamic bank and Bank Aceh Syariah as a regional Islamic bank using the Economic Value Added (EVA) framework over the period 2019–2024. Adopting a quantitative comparative design, the study utilizes secondary data derived from the annual financial reports of both institutions. The analysis operationalizes financial performance through key EVA components, including Net Operating Profit After Tax (NOPAT), Invested Capital (IC), Weighted Average Cost of Capital (WACC), and Capital Charge (CC), to assess value creation beyond conventional profitability measures.The results show that BSI consistently generates positive and increasing EVA, indicating sustained value creation and superior capital efficiency. In contrast, Bank Aceh Syariah exhibits fluctuating EVA performance, including a negative value in 2019, followed by positive but unstable trends in subsequent years. These differences highlight structural disparities in managerial effectiveness, scale efficiency, and capital allocation between national and regional Islamic banks. This study contributes to the literature by extending the application of the EVA framework within the context of Islamic banking, particularly through a comparative analysis of national and regional institutions—an area that remains underexplored. The findings reinforce the relevance of value-based performance measurement in assessing Islamic financial institutions and provide important implications for policymakers and bank management in enhancing efficiency, strengthening governance, and supporting sustainable regional economic development.